High-elastic wear-resistant fabric and preparation method thereof

By covering the polyetheride membrane and the chlorine -resistant additives on the spandex fabrics, the problem of poor chlorine resistance when the spandex fabric is exposed to the chlorine -containing coated agent, and achieves high elasticity, anti -static and wear -resistant fabric performance.

CN114990898BActive Publication Date: 2025-01-24SHANGHAI BONO CLOTHING
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210651144.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-09
Publication Date
2025-01-24
Estimated Expiration
2042-06-09

AI Technical Summary

Technical Problem

Existing spandex fabrics have poor chlorine resistance when exposed to chlorine-containing laundry agents or bleaches, resulting in reduced elasticity and product damage, and lack of anti-static properties.

Method used

By covering polyetheride membranes on the spandex fabric, and adding chlorine -resistant additives during the spinning process, specifically to introduce fluoride and pyridine into double -water popthyde plug -in water stones to enhance the chlorine resistance and of the spandex fiber and Anti -static electrostatic, and fixed polyetheride membrane through optical curing technology.

Benefits of technology

It significantly improves the chlorine resistance and anti -static properties of the spandex fabric, and at the same time enhances the wear resistance of the fabric and extend the service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-elastic wear-resistant fabric and a preparation method thereof, and relates to the field of textile technology. When preparing the high-elastic wear-resistant fabric, the invention adds a chlorine-resistant additive during the spinning process to obtain spandex fiber, weaves it into spandex fabric, and then covers it with a polyetheramide film for light curing; the chlorine-resistant additive can enhance the chlorine resistance and antibacterial properties, while forming a passage inside the spandex fiber, so that the spandex fiber has antistatic properties; the dendritic polyetheramide contains a large number of hydroxyl groups, which can be connected to the surface of carboxylated graphene, so that the polyetheramide film forms a cross-linked structure and covers the spandex fabric, reacts with the spandex fabric for cross-linking, and solidifies the polyetheramide film and connects it to the surface of the spandex fabric, thereby enhancing the wear resistance of the fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of textiles, in particular to a high-elastic wear-resistant fabric and a preparation method thereof. Background Art

[0002] Fabrics are materials used to make clothing. There are many types of fabrics, and most of them are comfortable to wear, sweat-absorbent and breathable. As people pay more and more attention to health and sports, daily wear and tear of clothing is gradually increasing; especially for some consumers who love fitness and outdoor sports, they have higher and higher requirements for the wear resistance of clothing fabrics.

[0003] The high elasticity of spandex fabrics is very comfortable for consumers, but a major drawback of spandex products is poor chlorine resistance. Chlorine-containing laundry detergents and bleaches on the market can damage spandex products, and the resulting swimsuits will also have the disadvantage of reduced elasticity after long-term use in swimming pools. The reason for the poor chlorine resistance of spandex is that chlorine atoms will replace hydrogen atoms on the amide structure, and the new "chloramines" will make the products yellow and reduce their strength. Therefore, the present invention studies and prepares a chlorine-resistant, antistatic, high-elastic and wear-resistant fabric. Summary of the invention

[0004] The object of the present invention is to provide a high-elastic wear-resistant fabric and a preparation method thereof to solve the problems raised in the above background technology.

[0005] A high-elastic wear-resistant fabric is prepared by coating a spandex fabric with a polyetheramide film and then performing light curing.

[0006] Preferably, the spandex fabric is made by weaving spandex fibers; the spandex fibers are made by solution dry spinning of polytetramethylene ether glycol, diphenylmethane-4,4'-diisocyanate and a chlorine-resistant additive.

[0007] Preferably, the chlorine-resistant additive is prepared by introducing fluorinated heterocyclic pyridine into disalicylicaldehyde intercalated hydrotalcite; the fluorinated heterocyclic pyridine is prepared by oxidizing the cyano group on 2,6-dichloro-3-cyano-5-fluoropyridine to a carboxyl group.

[0008] Preferably, the polyetheramide membrane is prepared by connecting dendritic polyetheramide on the surface of carboxylated graphene; the dendritic polyetheramide is prepared by reacting tetramethylol glycoluril with acrylonitrile, and then reacting with ethanol and trimethylolaminomethane under strong acid catalysis.

[0009] Preferably, the method for preparing the highly elastic and wear-resistant fabric comprises the following specific steps:

[0010] (1) 0.8 mol / L zinc nitrate, 0.4 mol / L aluminum nitrate and 0.4 mol / L magnesium nitrate were mixed in a volume ratio of 2:1:1 to prepare a salt solution; 5.12 mol / L sodium hydroxide and 1 mol / L sodium carbonate amine were mixed in a volume ratio of 3:1 to 4:1 to prepare an alkaline solution; dispersing salicylaldehyde in deionized water with a mass of 10 to 15 times that of salicylaldehyde, and ultrasonically dispersing at 50 to 80 kHz for 5 min. ~8min, and after heating to 80~100℃, the salt solution and the alkali solution are added dropwise at a rate of 3~5ml / min, the mass ratio of disalicylicaldehyde, the salt solution and the alkali solution is 0.1:4:3~0.15:4:3, and the pH is maintained at 8~9 with sodium hydroxide solution. After the addition is completed, it is filtered, crystallized at 60~70℃ for 24h, and then washed with deionized water for 5~8 times, and finally dried at 60~70℃ for 24h, and ground through a 300-mesh sieve to obtain disalicylicaldehyde intercalated hydrotalcite;

[0011] (2) mixing the disalicylic aldehyde intercalated hydrotalcite with a sodium hydroxide solution having a mass fraction of 5 to 10% at a mass ratio of 1:15 to 1:20, adding fluorinated heterocyclic pyridine having a mass fraction of 1.12 to 1.15 times that of the disalicylic aldehyde intercalated hydrotalcite, heating to 80 to 90° C., and adding a sodium hydroxide solution having a mass fraction of 5 to 10% having a mass fraction of 3 to 8 times that of the disalicylic aldehyde intercalated hydrotalcite at a rate of 2 to 3 ml / min, and keeping the reaction warm for 18 to 24 hours, filtering and washing with deionized water for 5 to 8 times, and drying at 60 to 70° C. for 12 hours to obtain a chlorine-resistant additive;

[0012] (3) In a nitrogen atmosphere, polytetramethylene ether glycol and diphenylmethane-4,4'-diisocyanate are mixed in a mass ratio of 1:4 to 1:5, heated to 85 to 90°C, stirred at 300 to 500 rpm for reaction for 5 to 8 hours, cooled to room temperature, added with 5 to 12 times the mass of polytetramethylene ether glycol, N,N-dimethylacetamide, and then added dropwise at a rate of 3 to 5 ml / min with 0.05 to 0.15 times the mass of polytetramethylene ether glycol. The reaction is continued with stirring for 1 to 2 hours, and a chlorine-resistant additive is added with 0.8 to 1.2 times the mass of polytetramethylene ether glycol. The reaction is continued with stirring for 1 to 2 hours to obtain a spinning solution;

[0013] (4) subjecting the spinning solution to solution dry spinning to obtain spandex fiber; weaving the spandex fiber to obtain a fiber having a gram weight of 150 to 300 g / m 2 Spandex fabric;

[0014] (5) Tetramethylol glycoluril, acrylonitrile, tetraethylammonium hydroxide and deionized water are mixed in a mass ratio of 1:3:0.2:10 to 1:3.5:0.4:15, stirred evenly, heated to 80 to 100°C, reacted for 5 to 8 hours, cooled to room temperature, added with anhydrous ethanol in an amount of 1 to 1.25 times the mass of acrylonitrile and sulfuric acid in an amount of 98% by mass in an amount of 0.2 to 0.4 times the mass of acrylonitrile, continued to react for 15 to 18 hours, added with tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide, the mass ratio of acrylonitrile, tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide being 1:4:0.3:10 to 1:6:0.4:20, reacted for 8 to 12 hours, and obtained a dendritic polyether amide;

[0015] (6) Adding carboxylated graphene in an amount of 0.15 to 0.3 times the mass of the dendritic polyether amide to the dendritic polyether amide, stirring evenly and heating to 60 to 80° C., adding sulfuric acid in an amount of 98% by mass, which is 0.1 to 0.2 times the mass of the dendritic polyether amide, and continuing the reaction for 10 to 20 hours to obtain a polyether amide film; coating the polyether amide film on the surface of a spandex fabric with a thickness of 50 to 80 μm, irradiating with ultraviolet light, with a wavelength of 320 nm to 400 nm, and an irradiation time of 20 to 30 minutes, to obtain a highly elastic and wear-resistant fabric.

[0016] Preferably, in the above step (1): the preparation method of disalicylic aldehyde is: under a nitrogen atmosphere, bisphenol A, sodium hydroxide, ethylene glycol and deionized water are mixed in a mass ratio of 1:3:7:25 to 1.1:3:7:28, and a chloroform mixed liquid with a mass of 1.6 to 1.8 times that of bisphenol A is added dropwise at a rate of 1 to 2 ml / min, wherein the volume ratio of chloroform to triethylamine in the chloroform mixed liquid is 4:1 to 5:1, heating to 80 to 100° C. and reflux reaction for 9 to 11 hours, cooling to room temperature, adjusting the pH to 6.8 to 7.2 with hydrochloric acid, extracting and concentrating with dichloromethane, and then separating and purifying by column chromatography to obtain disalicylic aldehyde.

[0017] Preferably, in the above step (2): the preparation method of the fluorinated heterocyclic pyridine is: 2,6-dihydroxy-3-cyano-5-fluoropyridine and phosphorus trichloride are mixed in a mass ratio of 12:1 to 15:1 and stirred evenly, 3 to 5 times the mass of the phosphorus trichloride catalyst N,N-dimethylaniline is added dropwise at a rate of 3 to 5 ml / min, and the mixture is heated to boiling and then kept warm for 6 to 10 hours, 5 to 10 times the mass of the phosphorus trichloride and 98% concentrated sulfuric acid is added, the reaction is continued for 5 to 8 hours, and the mixture is distilled under reduced pressure, allowed to stand for 12 to 14 hours, filtered and recrystallized with an ethanol solution with a mass fraction of 50% to obtain the fluorinated heterocyclic pyridine.

[0018] Preferably, in the above step (4): during the solution dry spinning, the air volume in the tunnel is 630-750m 3 / h, temperature is 240-250℃, and drawing ratio is 1.1-1.2.

[0019] Preferably, in the above step (5): the preparation method of tetrakishydroxymethyl glycoluril is: add glyoxal dropwise to a urea solution with a pH value of 1 to 2 and a mass fraction of 8 to 12%, the dropwise addition rate is 1 to 3 ml / min, the temperature is maintained at 40 to 60° C., the mass ratio of urea solution to glyoxal is 8:1 to 10:1, react for 5 to 6 hours after the dropwise addition is completed, filter and wash with sodium hydroxide solution and deionized water 2 to 3 times in sequence to obtain glycoluril; mix glycoluril and formaldehyde in a mass ratio of 1:1.5 to 1:2, adjust the pH to 9.5 to 10 with sodium hydroxide solution, heat to 50 to 60° C., react for 1 to 2 hours, heat to 65 to 68° C., perform reduced pressure distillation, and finally precipitate with methanol, filter and wash with methanol 2 to 3 times, and dry at 60 to 70° C. for 5 to 8 hours to obtain tetrakishydroxymethyl glycoluril.

[0020] Preferably, in the above step (6): the preparation method of carboxylated graphene is: graphene oxide and deionized water are mixed in a mass ratio of 1:100 and ultrasonically dispersed at 50-80kHz for 0.5-1h, sodium hydroxide in an amount of 8-10 times the mass of graphene oxide is added, and ultrasonication is continued for 0.5-1h, and bromoacetic acid in an amount of 15-20 times the mass of graphene oxide is added, and ultrasonic dispersion is continued for 15-30min. After reacting for 5-8h, centrifugation, washing, suction filtration, and vacuum drying are performed to obtain carboxylated graphene.

[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0022] When preparing the high-elastic wear-resistant fabric, the present invention adds a chlorine-resistant additive during the spinning process to obtain spandex fibers, which are woven into spandex fabrics and then coated with a polyetheramide film for light curing.

[0023] The chlorine-resistant additive is prepared by introducing fluorinated heterocyclic pyridine into the hydrotalcite intercalated with disalicylic aldehyde; the fluorinated heterocyclic pyridine is prepared by oxidizing the cyano group on 2,6-dichloro-3-cyano-5-fluoropyridine to a carboxyl group, and the fluorinated heterocyclic pyridine is then reacted with the disalicylic aldehyde precipitated and intercalated between the layers of the magnesium-aluminum hydrotalcite to obtain the chlorine-resistant additive. When preparing spandex fiber, adding hydrotalcite during the spinning process can enhance the chlorine resistance, and introducing salicylaldehyde groups after intercalating disalicylic aldehyde, which can react with various forms of active chlorine, prevents the formation of chloramines on the surface of the spandex, and further enhances the chlorine resistance; the fluorinated heterocyclic pyridine is then connected to the disalicylic aldehyde, so that the spandex fiber has antibacterial properties, and a passage is formed inside the spandex fiber, increasing the distance between the hydrotalcite layers, so that the spandex fiber has antistatic properties;

[0024] The polyetheramide membrane is prepared by connecting dendritic polyetheramide to the surface of carboxylated graphene; the dendritic polyetheramide is prepared by reacting tetrakis(hydroxymethyl)glycoluril with acrylonitrile, and then reacting with ethanol and tris(hydroxymethyl)aminomethane under strong acid catalysis. The dendritic polyetheramide contains a large number of hydroxyl groups and can be connected to the surface of carboxylated graphene, so that the three-dimensional molecular structure of the dendritic polyetheramide is closely arranged and forms a cross-linked structure to be coated on the spandex fabric. The dendritic polyetheramide prepared by tetrakis(hydroxymethyl)glycoluril can react and cross-link with the spandex fabric, and the polyetheramide membrane is solidified and connected to the surface of the spandex fabric to form a protective layer with nano-protrusions, thereby enhancing the wear resistance of the fabric. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the high-elastic wear-resistant fabrics prepared in the examples and comparative examples as follows:

[0027] Chlorine resistance: After the examples and comparative examples were stretched by 50%, they were immersed in a bath with an effective chlorine concentration of 20 ppm (pH = 7), and the strength after 48 hours was measured with reference to GB / T3923.1, and the strength retention was compared;

[0028] Antistatic property: The charge surface density test of the embodiments and comparative examples was carried out according to GB / T12703.2.

[0029] Wear resistance: The wear resistance of the embodiments and comparative examples was tested using a GX-5028-DIN abrasion tester.

[0030] Example 1

[0031] (1) In a nitrogen atmosphere, bisphenol A, sodium hydroxide, ethylene glycol and deionized water are mixed in a mass ratio of 1:3:7:25, and a chloroform mixture with a mass of 1.6 times that of bisphenol A is added dropwise at a rate of 1 ml / min, wherein the volume ratio of chloroform to triethylamine in the chloroform mixture is 4:1. The mixture is heated to 80° C. and refluxed for 9 hours. After cooling to room temperature, the pH value is adjusted to 6.8 with hydrochloric acid, extracted and concentrated with dichloromethane, and then separated and purified by column chromatography to obtain disalicylic aldehyde; zinc nitrate with a concentration of 0.8 mol / L, aluminum nitrate with a concentration of 0.4 mol / L and magnesium nitrate with a concentration of 0.4 mol / L are mixed evenly in a volume ratio of 2:1:1 to obtain a salt solution. ; Mix 5.12 mol / L sodium hydroxide and 1 mol / L sodium carbonate amine in a volume ratio of 3:1 to prepare an alkaline solution; disperse disalicylic aldehyde in deionized water 10 times the mass of disalicylic aldehyde, ultrasonically disperse it at 50 kHz for 5 minutes, and heat it to 80°C, then simultaneously add salt solution and alkaline solution at a rate of 3 ml / min, the mass ratio of disalicylic aldehyde, salt solution and alkaline solution is 0.1:4:3, and keep the pH at 8 with sodium hydroxide solution. After the addition is completed, filter, crystallize at 60°C for 24 hours, wash with deionized water 5 times, and finally dry at 60°C for 24 hours, grind through a 300-mesh sieve to prepare disalicylic aldehyde intercalated hydrotalcite;

[0032] (2) 2,6-dihydroxy-3-cyano-5-fluoropyridine and phosphorus trichloride were mixed at a mass ratio of 12:1 and stirred evenly, and a catalyst N,N-dimethylaniline in an amount 3 times the mass of phosphorus trichloride was added dropwise at a rate of 3 ml / min, and the mixture was heated to boiling and then kept warm for 6 hours. Concentrated sulfuric acid in an amount 5 times the mass of phosphorus trichloride and having a mass fraction of 98% was added, and the reaction was continued for 5 hours. The mixture was distilled under reduced pressure, allowed to stand for 12 hours, filtered, and recrystallized with an ethanol solution having a mass fraction of 50% to obtain a fluorine-containing Heterocyclic pyridine; mixing disalicylic aldehyde intercalated hydrotalcite and 5% sodium hydroxide solution at a mass ratio of 1:15, adding fluorinated heterocyclic pyridine in an amount of 1.12 times the mass of disalicylic aldehyde intercalated hydrotalcite, heating to 80°C, and dropping 5% sodium hydroxide solution in an amount of 3 times the mass of disalicylic aldehyde intercalated hydrotalcite at a rate of 2 ml / min, keeping the reaction warm for 18 hours, filtering and washing with deionized water for 5 times, and drying at 60°C for 12 hours to obtain a chlorine-resistant additive;

[0033] (3) In a nitrogen atmosphere, polytetramethylene ether glycol and diphenylmethane-4,4'-diisocyanate were mixed in a mass ratio of 1:4, heated to 85°C, stirred at 300 rpm for reaction for 5 hours, cooled to room temperature, added N,N-dimethylacetamide with a mass of 5 times that of polytetramethylene ether glycol, and then ethylenediamine with a mass of 0.05 times that of polytetramethylene ether glycol was added dropwise at a rate of 3 ml / min, and the reaction was continued with stirring for 1 hour, and a chlorine-resistant additive with a mass of 0.8 times that of polytetramethylene ether glycol was added, and the reaction was continued with stirring for 1 hour to obtain a spinning solution;

[0034] (4) The spinning solution is subjected to solution dry spinning, and the air volume in the tunnel is 630m 3 / h, temperature of 240 ° C, draft ratio of 1.1, to obtain spandex fiber; the spandex fiber was spun to obtain a weight of 150g / m 2 Spandex fabric;

[0035] (5) Glyoxal was added dropwise to a urea solution with a pH value of 1 and a mass fraction of 8% at a rate of 1 ml / min, the temperature was maintained at 40° C., the mass ratio of urea solution to glyoxal was 8:1, and the mixture was reacted for 5 h after the addition was completed, filtered and washed twice with sodium hydroxide solution and deionized water in sequence to obtain glycoluril; glycoluril and formaldehyde were mixed at a mass ratio of 1:1.5, the pH was adjusted to 9.5 with sodium hydroxide solution, heated to 50° C., reacted for 1 h, heated to 65° C., distilled under reduced pressure, and finally precipitated with methanol, filtered and washed twice with methanol, and dried at 60° C. for 5 min. h, tetramethylol glycoluril is obtained; tetramethylol glycoluril, acrylonitrile, tetraethylammonium hydroxide and deionized water are mixed in a mass ratio of 1:3:0.2:10, stirred evenly, heated to 80°C, reacted for 5 h, cooled to room temperature, anhydrous ethanol 1 times the mass of acrylonitrile and sulfuric acid 0.2 times the mass of acrylonitrile with a mass fraction of 98% are added, the reaction is continued for 15 h, trimethylolaminomethane, potassium carbonate and dimethyl sulfoxide are added, the mass ratio of acrylonitrile, trimethylolaminomethane, potassium carbonate and dimethyl sulfoxide is 1:4:0.3:10, reacted for 8 h, and a dendritic polyether amide is obtained;

[0036] (6) Graphene oxide and deionized water were mixed in a mass ratio of 1:100 and ultrasonically dispersed at 50 kHz for 0.5 h, and sodium hydroxide 8 times the mass of graphene oxide was added, and ultrasonication was continued for 0.5 h. Then, bromoacetic acid 15 times the mass of graphene oxide was added, and ultrasonic dispersion was continued for 15 to 30 min. After reacting for 5 h, centrifugation, washing, suction filtration, and vacuum drying were performed to obtain carboxylated graphene; 0.15 times the mass of dendritic polyether amide was added to the carboxylated graphene, the mixture was stirred evenly and heated to 60° C., 0.1 times the mass of dendritic polyether amide was added with sulfuric acid having a mass fraction of 98%, and the reaction was continued for 10 h to obtain a polyether amide film; the polyether amide film was coated on the surface of a spandex fabric with a thickness of 50 μm, and irradiated with ultraviolet light with a wavelength of 320 nm for 20 min to obtain a highly elastic and wear-resistant fabric.

[0037] Example 2

[0038] (1) In a nitrogen atmosphere, bisphenol A, sodium hydroxide, ethylene glycol and deionized water are mixed in a mass ratio of 1:3:7:27, and a chloroform mixture with a mass of 1.7 times that of bisphenol A is added dropwise at a rate of 1 ml / min, wherein the volume ratio of chloroform to triethylamine in the chloroform mixture is 4.5:1. The mixture is heated to 90° C. and refluxed for 10 h. After cooling to room temperature, the pH value is adjusted to 7 with hydrochloric acid, extracted with dichloromethane, concentrated, and separated and purified by column chromatography to obtain disalicylic aldehyde; zinc nitrate with a concentration of 0.8 mol / L, aluminum nitrate with a concentration of 0.4 mol / L and magnesium nitrate with a concentration of 0.4 mol / L are mixed uniformly in a volume ratio of 2:1:1 to obtain a salt solution; and a concentration of 5.12 mol / L sodium hydroxide and 1 mol / L sodium carbonate amine are mixed in a volume ratio of 3.5:1 to prepare an alkaline solution; dispersing dissalicylaldehyde in deionized water with a mass of 10 to 15 times that of dissalicylaldehyde, ultrasonically dispersing at 60 kHz for 6 minutes, and heating to 90°C, and then dropping a salt solution and an alkaline solution at a rate of 3 to 5 ml / min at the same time, the mass ratio of dissalicylaldehyde, salt solution and alkaline solution is 0.13:4:3, and maintaining the pH at 8.5 with a sodium hydroxide solution. After the addition is completed, filtering is performed, crystallizing at 65°C for 24 hours, and then washing with deionized water for 6 times, and finally drying at 65°C for 24 hours, grinding through a 300-mesh sieve, and preparing dissalicylaldehyde intercalated hydrotalcite;

[0039] (2) 2,6-dihydroxy-3-cyano-5-fluoropyridine and phosphorus trichloride were mixed at a mass ratio of 14:1 and stirred evenly, and a catalyst N,N-dimethylaniline in an amount of 4 times the mass of phosphorus trichloride was added dropwise at a rate of 4 ml / min, and the mixture was heated to boiling and then kept warm for 8 hours. Concentrated sulfuric acid in an amount of 98% in an amount of 8 times the mass of phosphorus trichloride was added, and the reaction was continued for 6 hours. The mixture was distilled under reduced pressure, allowed to stand for 13 hours, filtered, and recrystallized with an ethanol solution in an amount of 50% by mass to obtain a fluorine-containing Heterocyclic pyridine; mixing disalicylic aldehyde intercalated hydrotalcite and 8% sodium hydroxide solution at a mass ratio of 1:18, adding fluorinated heterocyclic pyridine in an amount of 1.14 times the mass of disalicylic aldehyde intercalated hydrotalcite, heating to 85°C, and dropping 8% sodium hydroxide solution in an amount of 5 times the mass of disalicylic aldehyde intercalated hydrotalcite at a rate of 2 ml / min, keeping the reaction warm for 20 hours, filtering and washing with deionized water for 6 times, and drying at 65°C for 12 hours to obtain a chlorine-resistant additive;

[0040] (3) In a nitrogen atmosphere, polytetramethylene ether glycol and diphenylmethane-4,4'-diisocyanate are mixed in a mass ratio of 1:4.5, heated to 88°C, stirred at 400 rpm for 6 hours, cooled to room temperature, added with 5 to 12 times the mass of polytetramethylene ether glycol, N,N-dimethylacetamide, and then added dropwise at a rate of 3 to 5 ml / min with 0.1 times the mass of polytetramethylene ether glycol ethylenediamine, continued to stir and react for 1.5 hours, added with 1 times the mass of polytetramethylene ether glycol chlorine-resistant additive, continued to stir and react for 1.5 hours, and obtained a spinning solution;

[0041] (4) The spinning solution is subjected to solution dry spinning, and the air volume in the tunnel is 700m 3 / h, temperature of 245 ° C, draft ratio of 1.15, to obtain spandex fiber; the spandex fiber was spun to obtain a weight of 240g / m 2 Spandex fabric;

[0042] (5) Glyoxal was added dropwise to a urea solution with a pH value of 1.5 and a mass fraction of 10% at a rate of 2 ml / min, the temperature was maintained at 50° C., the mass ratio of urea solution to glyoxal was 9:1, and the reaction was continued for 5 h after the addition was completed, and the mixture was filtered and washed twice with sodium hydroxide solution and deionized water in sequence to obtain glycoluril; glycoluril and formaldehyde were mixed at a mass ratio of 1:1.8, the pH was adjusted to 9.8 with sodium hydroxide solution, heated to 55° C., reacted for 1.5 h, heated to 66° C., distilled under reduced pressure, and finally precipitated with methanol, filtered and washed twice with methanol, and dried at 65° C. for 6 h. Tetramethylol glycoluril is prepared; tetramethylol glycoluril, acrylonitrile, tetraethylammonium hydroxide and deionized water are mixed in a mass ratio of 1:3.2:0.3:13, stirred evenly, heated to 90°C, reacted for 6 hours, cooled to room temperature, anhydrous ethanol 1.15 times the mass of acrylonitrile and sulfuric acid 0.2-0.4 times the mass of acrylonitrile with a mass fraction of 98% are added, the reaction is continued for 16 hours, tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide are added, the mass ratio of acrylonitrile, tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide is 1:5:0.3:15, reacted for 10 hours, and a dendritic polyether amide is prepared;

[0043] (6) Graphene oxide and deionized water were mixed in a mass ratio of 1:100 and ultrasonically dispersed at 50-80kHz for 0.5h, sodium hydroxide was added in an amount of 9 times the mass of graphene oxide, and ultrasonic dispersion was continued for 0.5h, and bromoacetic acid was added in an amount of 18 times the mass of graphene oxide, and ultrasonic dispersion was continued for 25min. After reacting for 6h, the mixture was centrifuged, washed, filtered, and vacuum dried to obtain carboxylated graphene; carboxylated graphene in an amount of 0.25 times the mass of dendritic polyether amide was added to the dendritic polyether amide, stirred evenly and heated to 70°C, sulfuric acid in an amount of 0.15 times the mass of the dendritic polyether amide with a mass fraction of 98% was added, and the reaction was continued for 15h to obtain a polyether amide film; the polyether amide film was coated on the surface of a spandex fabric with a thickness of 70μm, and irradiated with ultraviolet light with a wavelength of 400nm and an irradiation time of 25min to obtain a highly elastic and wear-resistant fabric.

[0044] Example 3

[0045] (1) In a nitrogen atmosphere, bisphenol A, sodium hydroxide, ethylene glycol and deionized water are mixed in a mass ratio of 1.1:3:7:28, and a chloroform mixture with a mass of 1.8 times that of bisphenol A is added dropwise at a rate of 2 ml / min, wherein the volume ratio of chloroform to triethylamine in the chloroform mixture is 5:1. The mixture is heated to 100° C. and refluxed for 11 hours. After cooling to room temperature, the pH value is adjusted to 7.2 with hydrochloric acid, extracted with dichloromethane, concentrated, and then separated and purified by column chromatography to obtain disalicylic aldehyde; zinc nitrate with a concentration of 0.8 mol / L, aluminum nitrate with a concentration of 0.4 mol / L and magnesium nitrate with a concentration of 0.4 mol / L are uniformly mixed in a volume ratio of 2:1:1 to obtain a salt solution. liquid; sodium hydroxide with a concentration of 5.12 mol / L and sodium carbonate amine with a concentration of 1 mol / L in a volume ratio of 4:1 to prepare an alkaline solution; dispersing dissalicylaldehyde in deionized water with a mass of 15 times that of dissalicylaldehyde, ultrasonically dispersing at 80 kHz for 8 minutes, and heating to 100°C, and then dropping a salt solution and an alkaline solution at a rate of 5 ml / min at the same time, the mass ratio of dissalicylaldehyde, the salt solution and the alkaline solution is 0.15:4:3, and the pH is maintained at 9 with a sodium hydroxide solution. After the addition is completed, filtering is performed, crystallizing at 70°C for 24 hours, and then washing with deionized water for 8 times, and finally drying at 70°C for 24 hours, grinding through a 300-mesh sieve, and obtaining dissalicylaldehyde intercalated hydrotalcite;

[0046] (2) 2,6-dihydroxy-3-cyano-5-fluoropyridine and phosphorus trichloride are mixed in a mass ratio of 12:1 to 15:1 and stirred evenly, and a catalyst N,N-dimethylaniline in an amount of 5 times the mass of phosphorus trichloride is added dropwise at a rate of 5 ml / min, and the mixture is heated to boiling and then kept warm for 10 hours. Concentrated sulfuric acid in an amount of 98% by mass and 10 times the mass of phosphorus trichloride is added, and the reaction is continued for 8 hours. The mixture is distilled under reduced pressure, allowed to stand for 14 hours, filtered, and recrystallized with an ethanol solution in an amount of 50% by mass to prepare a The fluorinated heterocyclic pyridine was obtained; the disalicylic aldehyde intercalated hydrotalcite was mixed with a 10% sodium hydroxide solution at a mass ratio of 1:20, 1.15 times the mass of the disalicylic aldehyde intercalated hydrotalcite of the fluorinated heterocyclic pyridine was added, and the mixture was heated to 90°C, and 8 times the mass of the disalicylic aldehyde intercalated hydrotalcite of the 10% sodium hydroxide solution was added dropwise at a rate of 3 ml / min, and the mixture was kept warm for 24 hours, filtered, washed with deionized water for 8 times, and dried at 70°C for 12 hours to obtain a chlorine-resistant additive;

[0047] (3) In a nitrogen atmosphere, polytetramethylene ether glycol and diphenylmethane-4,4'-diisocyanate were mixed in a mass ratio of 1:5, heated to 90°C, stirred at 500 rpm for 8 hours, cooled to room temperature, added N,N-dimethylacetamide (12 times the mass of polytetramethylene ether glycol), and then ethylenediamine (0.15 times the mass of polytetramethylene ether glycol) was added dropwise at a rate of 5 ml / min, and the stirring reaction was continued for 2 hours. A chlorine-resistant additive (1.2 times the mass of polytetramethylene ether glycol) was added, and the stirring reaction was continued for 2 hours to obtain a spinning solution;

[0048] (4) The spinning solution is subjected to solution dry spinning, and the air volume in the tunnel is 750m 3 / h, the temperature is 250℃, the draft ratio is 1.2, and the spandex fiber is obtained; the spandex fiber is spun to obtain a weight of 300g / m 2 Spandex fabric;

[0049] (5) Glyoxal was added dropwise to a urea solution with a pH value of 2 and a mass fraction of 12% at a rate of 3 ml / min, the temperature was maintained at 60° C., the mass ratio of urea solution to glyoxal was 10:1, and the reaction was continued for 6 hours after the addition was completed, and the mixture was filtered and washed with sodium hydroxide solution and deionized water three times in sequence to obtain glycoluril; glycoluril and formaldehyde were mixed at a mass ratio of 1:2, the pH was adjusted to 10 with sodium hydroxide solution, heated to 60° C., reacted for 2 hours, heated to 68° C., distilled under reduced pressure, and finally precipitated with methanol, filtered and washed with methanol three times, and dried at 70° C. for 8 hours to obtain Tetramethylol glycoluril; Tetramethylol glycoluril, acrylonitrile, tetraethylammonium hydroxide and deionized water are mixed in a mass ratio of 1:3.5:0.4:15, stirred evenly, heated to 100°C, reacted for 8 hours, cooled to room temperature, added with anhydrous ethanol 1.25 times the mass of acrylonitrile and sulfuric acid 0.4 times the mass of acrylonitrile with a mass fraction of 98%, continued to react for 18 hours, added with tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide, the mass ratio of acrylonitrile, tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide being 1:6:0.4:20, reacted for 12 hours, and obtained a dendritic polyether amide;

[0050] (6) Graphene oxide and deionized water were mixed in a mass ratio of 1:100 and ultrasonically dispersed at 80kHz for 1 hour, and sodium hydroxide with a mass of 10 times that of the graphene oxide was added, and ultrasonic dispersion was continued for 1 hour. Then, bromoacetic acid with a mass of 20 times that of the graphene oxide was added, and ultrasonic dispersion was continued for 30 minutes. After reacting for 8 hours, centrifugation, washing, suction filtration, and vacuum drying were performed to obtain carboxylated graphene; 0.3 times the mass of the dendritic polyether amide was added to the dendritic polyether amide, carboxylated graphene was added, the mixture was stirred evenly and heated to 80°C, and 0.2 times the mass of the dendritic polyether amide was added with sulfuric acid with a mass fraction of 98%, and the reaction was continued for 20 hours to obtain a polyether amide film; the polyether amide film was coated on the surface of the spandex fabric with a thickness of 80 μm, and ultraviolet light was irradiated with a wavelength of 400 nm for 30 minutes to obtain a highly elastic and wear-resistant fabric.

[0051] Comparative Example 1

[0052] The prescription composition of comparative example 1 is the same as that of example 2. The difference between the preparation method of the high elastic wear-resistant fabric and example 2 is that the treatment of step (1) is not performed, and the disalicylicylaldehyde intercalated hydrotalcite prepared in step (1) is the chlorine-resistant additive.

[0053] Comparative Example 2

[0054] The prescription composition of comparative example 2 is the same as that of example 2. The preparation method of the high elastic wear-resistant fabric is different from that of example 2 only in that step (2) is not performed, and step (1) is modified as follows: zinc nitrate with a concentration of 0.8 mol / L, aluminum nitrate with a concentration of 0.4 mol / L, and magnesium nitrate with a concentration of 0.4 mol / L are mixed uniformly in a volume ratio of 2:1:1 to obtain a salt solution; sodium hydroxide with a concentration of 5.12 mol / L and sodium carbonate amine with a concentration of 1 mol / L are mixed in a volume ratio of 3.5:1 to obtain an alkaline solution; the salt solution and the alkaline solution are added dropwise at a rate of 3 to 5 ml / min and heated to 90° C., the mass ratio of the salt solution to the alkaline solution is 4:3, and the pH is maintained at 8.5 with sodium hydroxide solution. After the addition is completed, the mixture is filtered, crystallized at 65° C. for 24 hours, washed with deionized water for 6 times, and finally dried at 65° C. for 24 hours, ground through a 300 mesh sieve, and hydrotalcite is obtained.

[0055] Comparative Example 3

[0056] The prescription composition of comparative example 3 is the same as that of example 2. The preparation method of the high elastic wear-resistant fabric is different from that of example 2 only in step (5), and step (5) is modified as follows: pentaerythritol, acrylonitrile, tetraethylammonium hydroxide and deionized water are mixed in a mass ratio of 1:3.2:0.3:13, stirred evenly, heated to 90°C, reacted for 6 hours, cooled to room temperature, anhydrous ethanol 1.15 times the mass of acrylonitrile and sulfuric acid 0.2-0.4 times the mass of acrylonitrile with a mass fraction of 98% are added, the reaction is continued for 16 hours, tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide are added, the mass ratio of acrylonitrile, tris(hydroxymethyl)aminomethane, potassium carbonate and dimethyl sulfoxide is 1:5:0.3:15, and after reacting for 10 hours, a dendritic polyether amide is obtained.

[0057] Comparative Example 4

[0058] The prescription composition of comparative example 4 is the same as that of example 2. The preparation method of the high elastic wear-resistant fabric is different from that of example 2 only in step (6), and step (6) is modified as follows: dendritic polyether amide is applied to the surface of spandex fabric with a thickness of 70 μm, and irradiated with ultraviolet light with a wavelength of 400 nm and an irradiation time of 25 min to obtain a high elastic wear-resistant fabric.

[0059] Comparative Example 5

[0060] The prescription composition of comparative example 5 is the same as that of example 2. The difference between the preparation method of the high elastic wear-resistant fabric and example 2 is that the treatment of steps (5) and (6) is not performed, and the spandex fabric prepared in step (4) is a high elastic wear-resistant fabric.

[0061] Effect example

[0062] Table 1 below shows the performance analysis results of the high elastic wear-resistant fabrics of Examples 1, 2, 3 of the present invention and Comparative Examples 1, 2, 3, 4, 5.

[0063] Table 1

[0064] Strength retention rate (%) <![CDATA[Surface charge density (uc / m 2 )]]> <![CDATA[Wear amount (mm 3 )]]> Example 1 93 3.89 64 Example 2 94 3.94 61 Example 3 92 3.57 52 Comparative Example 1 90 0.75 68 Comparative Example 2 79 0.84 66 Comparative Example 3 90 3.58 81 Comparative Example 4 92 3.14 84 Comparative Example 5 87 3.03 101

[0065] By comparing the experimental data of the examples and the comparative examples in Table 1, it can be clearly found that the high elastic wear-resistant fabrics prepared in Examples 1, 2, and 3 have good chlorine resistance, antistatic properties, and wear resistance;

[0066] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Examples 1, 2, 5, it can be found that the chlorine-resistant additive prepared by fluorinated heterocyclic pyridine is introduced into the hydrotalcite intercalated with disalicylic aldehyde to enhance the chlorine resistance, and the fluorinated heterocyclic pyridine is connected to the disalicylic aldehyde to form a passage inside the spandex fiber, thereby increasing the interlayer spacing of the hydrotalcite and making the spandex fiber have antistatic properties; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Examples 3, 4, 5, it can be found that the dendritic polyether amide contains a large number of hydroxyl groups and can be connected to the surface of carboxylated graphene, so that the three-dimensional molecular structure of the dendritic polyether amide is closely arranged, and a cross-linked structure is formed to be coated on the spandex fabric, and the dendritic polyether amide prepared by tetrakishydroxymethyl glycoluril can react and cross-link with the spandex fabric, and the polyether amide film is solidified and connected to the surface of the spandex fabric to form a protective layer with nano-protrusions, thereby enhancing the wear resistance of the fabric.

[0067] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a highly elastic and wear-resistant fabric, characterized in that: The preparation method of the highly elastic wear-resistant fabric comprises the following specific steps: (1) 0.8 mol / L zinc nitrate, 0.4 mol / L aluminum nitrate and 0.4 mol / L magnesium nitrate were mixed in a volume ratio of 2:1:1 to obtain a salt solution; 5.12 mol / L sodium hydroxide and 1 mol / L sodium carbonate were mixed in a volume ratio of 3:1-4:1 to obtain an alkaline solution; dispersing salicylaldehyde in deionized water with a mass of 10-15 times that of salicylaldehyde, ultrasonically dispersed at 50-80 kHz for 5-8 min, and heated to 80-100°C, and then adding the salt solution and the alkaline solution at a rate of 3-5 ml / min at the same time, wherein the mass ratio of salicylaldehyde, salt solution and alkaline solution was 0.1:4:3-0.15:4:3, and the pH was maintained at 8-9 with sodium hydroxide solution. After the addition was completed, Filter, crystallize at 60-70°C for 24h, wash with deionized water for 5-8 times, and finally dry at 60-70°C for 24h, grind through a 300-mesh sieve to obtain disalicylic aldehyde intercalated hydrotalcite; the preparation method of the above disalicylic aldehyde is: under a nitrogen atmosphere, bisphenol A, sodium hydroxide, ethylene glycol and deionized water are mixed in a mass ratio of 1:3:7:25-1.1:3:7:28, and a chloroform mixed solution with a mass of 1.6-1.8 times that of bisphenol A is added dropwise at a rate of 1-2ml / min, wherein the volume ratio of chloroform to triethylamine in the chloroform mixed solution is 4:1-5:1, heat to 80-100°C, reflux for reaction for 9-11h, cool to room temperature, adjust the pH to 6.8-7.2 with hydrochloric acid, extract and concentrate with dichloromethane, and then separate and purify by column chromatography to obtain disalicylic aldehyde; (2) mixing the disalicylic aldehyde intercalated hydrotalcite with a 5-10% sodium hydroxide solution at a mass ratio of 1:15-1:20, adding 1.12-1.15 times the mass of the disalicylic aldehyde intercalated hydrotalcite with a fluorinated heterocyclic pyridine, heating to 80-90°C, and adding 3-8 times the mass of the disalicylic aldehyde intercalated hydrotalcite with a 5-10% sodium hydroxide solution at a rate of 2-3 ml / min, keeping the reaction warm for 18-24 hours, filtering and washing with deionized water for 5-8 times, and drying at 60-70°C for 12 hours to obtain a chlorine-resistant additive; the above-mentioned fluorinated heterocyclic pyridine is added to the mixture, and the mixture is heated to 80-90°C. The preparation method of heterocyclic pyridine is as follows: 2,6-dihydroxy-3-cyano-5-fluoropyridine and phosphorus trichloride are mixed in a mass ratio of 12:1-15:1 and stirred evenly, N,N-dimethylaniline, a catalyst in an amount of 3-5 times the mass of phosphorus trichloride, is added dropwise at a rate of 3-5 ml / min, and the mixture is heated to boiling and then kept warm for reaction for 6-10 hours, concentrated sulfuric acid in an amount of 5-10 times the mass of phosphorus trichloride and having a mass fraction of 98% is added, the reaction is continued for 5-8 hours, vacuum distillation is performed, the mixture is allowed to stand for 12-14 hours, filtration is performed, and the mixture is recrystallized with an ethanol solution having a mass fraction of 50% to obtain a fluorinated heterocyclic pyridine; (3) In a nitrogen atmosphere, polytetramethylene ether glycol and diphenylmethane-4,4'-diisocyanate are mixed in a mass ratio of 1:4 to 1:5, heated to 85 to 90°C, stirred at 300 to 500 rpm for reaction for 5 to 8 hours, cooled to room temperature, added with 5 to 12 times the mass of polytetramethylene ether glycol, N,N-dimethylacetamide, and then added dropwise at a rate of 3 to 5 ml / min with 0.05 to 0.15 times the mass of polytetramethylene ether glycol, ethylenediamine, and continued to stir and react for 1 to 2 hours, added with 0.8 to 1.2 times the mass of polytetramethylene ether glycol, and continued to stir and react for 1 to 2 hours to obtain a spinning solution; (4) Dry spinning the spinning solution to obtain spandex fiber; weaving the spandex fiber to obtain a weight of 150-300 g / m 2 Spandex fabric; (5) Tetramethylol glycoluril, acrylonitrile, tetraethylammonium hydroxide and deionized water are mixed in a mass ratio of 1:3:0.2:10 to 1:3.5:0.4:15, stirred evenly, heated to 80 to 100°C, reacted for 5 to 8 hours, cooled to room temperature, added with anhydrous ethanol in an amount of 1 to 1.25 times the mass of acrylonitrile and sulfuric acid in an amount of 98% by mass in an amount of 0.2 to 0.4 times the mass of acrylonitrile, continued to react for 15 to 18 hours, added with trimethylolaminomethane, potassium carbonate and dimethyl sulfoxide, the mass ratio of acrylonitrile, trimethylolaminomethane, potassium carbonate and dimethyl sulfoxide being 1:4:0.3:10 to 1:6:0.4:20, reacted for 8 to 12 hours, and obtained a dendritic polyether amide; the preparation method of the above tetramethylol glycoluril The method comprises the following steps: adding glyoxal dropwise to a urea solution having a pH value of 1 to 2 and a mass fraction of 8 to 12%, with a dropping rate of 1 to 3 ml / min, maintaining the temperature at 40 to 60° C., and a mass ratio of urea solution to glyoxal of 8:1 to 10:

1. After the addition is completed, reacting for 5 to 6 hours, filtering with suction, and washing with sodium hydroxide solution and deionized water 2 to 3 times in sequence to obtain glycoluril; mixing glycoluril and formaldehyde in a mass ratio of 1:1.5 to 1:2, adjusting the pH to 9.5 to 10 with sodium hydroxide solution, heating to 50 to 60° C., reacting for 1 to 2 hours, heating to 65 to 68° C., performing reduced pressure distillation, and finally precipitating with methanol, filtering with suction, and then washing with methanol 2 to 3 times, and drying at 60 to 70° C. for 5 to 8 hours to obtain tetrahydroxymethyl glycoluril; (6) Add 0.15-0.3 times the mass of carboxylated graphene to the dendritic polyether amide, stir evenly and heat to 60-80°C, add 0.1-0.2 times the mass of the dendritic polyether amide and 98% sulfuric acid, continue to react for 10-20 hours, and obtain a polyether amide film; coat the polyether amide film on the surface of the spandex fabric with a thickness of 50-80 μm, and irradiate with ultraviolet light with a wavelength of 320 nm to 400 nm for 20-30 min to obtain a highly elastic and wear-resistant fabric.

2. The method for preparing a highly elastic and wear-resistant fabric according to claim 1, characterized in that: In the above step (4): during the solution dry spinning, the air volume in the tunnel is 630~750m 3 / h, temperature is 240~250℃, and drawing ratio is 1.1~1.

2.

3. The method for preparing a highly elastic and wear-resistant fabric according to claim 1, characterized in that: In the above step (6): the preparation method of carboxylated graphene is: graphene oxide and deionized water are mixed in a mass ratio of 1:100 and ultrasonically dispersed at 50-80 kHz for 0.5-1 h, sodium hydroxide in an amount of 8-10 times the mass of graphene oxide is added, and ultrasonication is continued for 0.5-1 h, and bromoacetic acid in an amount of 15-20 times the mass of graphene oxide is added, and ultrasonic dispersion is continued for 15-30 min. After reacting for 5-8 h, centrifugation, washing, suction filtration, and vacuum drying are performed to obtain carboxylated graphene.

Citation Information

Patent Citations

  • Process for manufacturing chlorine-resistant spandex fibre

    CN101096783A

  • Hydrophilic polyaramid composite membrane capable of resisting stain and chlorine, and preparation method thereof

    CN103908900A

  • Method for preparing graphene anticorrosive coating by loading and dispersing with dendritic polymer

    CN107880776A

  • Hydrotalcite intercalation chloride ion probe modified triazole corrosion inhibitor compound containing salicylaldehyde active group and application thereof

    CN107986661A

  • Sea-island structure chlorine-resistant polyurethane and preparation method thereof

    CN112127015A